1994
DOI: 10.1164/ajrccm.150.2.8049833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep deprivation and sleep fragmentation on upper airway collapsibility in normal subjects.

Abstract: Sleep deprivation can induce or worsen nocturnal respiratory disturbances. In patients with sleep apnea hypopnea, sleep abnormalities consist of repetitive episodes of arousals and awakenings that lead to sleep fragmentation. Because the propensity for upper airway collapse is increased in these patients, we wondered if sleep fragmentation could increase upper airway collapsibility and contribute to the pathogenesis of this disease. In eight normal subjects, upper airway collapsibility was assessed during slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(51 citation statements)
references
References 18 publications
1
46
2
2
Order By: Relevance
“…This has been noted in previous diurnal diagnostic studies and is usually explained by the effects of sleep deprivation [24][25][26]. However, the patients in this study were not sleep deprived.…”
Section: Discussionsupporting
confidence: 63%
“…This has been noted in previous diurnal diagnostic studies and is usually explained by the effects of sleep deprivation [24][25][26]. However, the patients in this study were not sleep deprived.…”
Section: Discussionsupporting
confidence: 63%
“…It is not clear which factors in this study diff ered from previous ones, but in this study, previous exposure to smoking was associated with worsening OSA. 26 Several studies found an association between smoking and self-reported sleep quality. Two studies used comprehensive sleep and health questionnaires to assess sleep quality.…”
Section: Methodsmentioning
confidence: 99%
“…39 Infants exposed to maternal smoking have reduced spontaneous and evoked arousability from sleep, again suggesting that the arousal threshold is impaired with exposure to smoke. 40 , 41 Although the higher arousal threshold (and therefore reduction in arousals) may result in less sleep instability and decreased upper airways collapsibility, 26 there may still be an eff ect on OSA. In a previously cited study of 1,492 adults referred for sleep evaluation, subjects who currently smoked exhibited a higher overall arousal index, but yet, during episodes of upper airways collapse, events were longer and desaturations were greater.…”
Section: Smoking and Upper Airway Neuromuscular Refl Exesmentioning
confidence: 99%
“…One possible explanation for such an effect is the reduction of mucosal oedema by minimising vibrational trauma, which is known to account for upper airway collapsibility, in part [26]. Another possible explanation is a reduction in sleep fragmentation, reflected by a further decrease in the arousalindex in the present study; sleep fragmentation is known to increase upper airway collapsibility [27,28]. A decrease in daytime somnolence may also be due to a better acclimatisation to CPAP and therefore less sleep fragmentation.…”
Section: Discussionmentioning
confidence: 57%